Pengaruh Lingkungan Kerja, Pelatihan dan Pengembangan Sumber Daya Manusia, Serta Kesehatan dan Keselamatan Kerja Terhadap Kinerja Karyawan PT. Sulawesi Resources Morowali - Andi Risma Melati; Ramly, Mansyur; Mahmud, Amid (AkMen JURNAL ILMIAH, 2024)
This study was conducted with the aim of analyzing the effect of work Environment, training and development of human resources and occupational health and safety on employee performance at PT Sulawesi Resources Morowali. This study uses primary data through a survey of 70 employees as a sample of the total number of employees, especially crew as many as 227 people, surveys from August-October. The results of this study indicate that the work environment, training and development of human resources, and occupational health and safety have a significant effect on the performance of employees of PT Sulawesi Resources Morowali.